Modernizing undergraduate medical education by bringing public health into focus - Hothersall, Eleanor J. (Frontiers in Public Health, 2024)
Healthcare and healthcare education are changing rapidly, being pulled in a number of directions by political, economic, environmental and technological imperatives. At the University of Dundee Medical School a curriculum review during the Covid-19 pandemic has allowed opportunities to reframe aspects of the program to emphasize themes linking public health and social determinants of health to the wider curriculum, while also bringing a shared understanding of the core outcomes of the program. This brings some adaptability into the structure and content of the course, helping graduates and staff to be “future proof.”